2016
DOI: 10.1038/nature19801
|View full text |Cite
|
Sign up to set email alerts
|

T-cell acute leukaemia exhibits dynamic interactions with bone marrow microenvironments

Abstract: It is widely accepted that complex interactions between cancer cells and their surrounding microenvironment contribute to disease development, chemo-resistance and disease relapse. In light of this observed interdependency, novel therapeutic interventions that target specific cancer stroma cell lineages and their interactions are being sought. To this end, we studied a mouse model of human T cell acute lymphoblastic leukaemia (T-ALL) and used intravital microscopy to monitor the progression of disease within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
167
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(181 citation statements)
references
References 36 publications
11
167
3
Order By: Relevance
“…Another study described the bone marrow seeding of leukaemia cells in vivo and their transient and promiscuous interactions with their microenvironment ( Fig. 2A; Hawkins et al, 2016). Here, IVM revealed a progressive remodelling of the bone marrow microenvironment during disease progression that was confirmed in biopsies from human patients, which emphasises the value of IVM in pre-clinical models to gain insights into disease aetiology (Hawkins et al, 2016).…”
Section: Box 1 Subcellular Imaging Techniquesmentioning
confidence: 93%
“…Another study described the bone marrow seeding of leukaemia cells in vivo and their transient and promiscuous interactions with their microenvironment ( Fig. 2A; Hawkins et al, 2016). Here, IVM revealed a progressive remodelling of the bone marrow microenvironment during disease progression that was confirmed in biopsies from human patients, which emphasises the value of IVM in pre-clinical models to gain insights into disease aetiology (Hawkins et al, 2016).…”
Section: Box 1 Subcellular Imaging Techniquesmentioning
confidence: 93%
“…Cristina showed that during infection, HSCs become either motile (although not mobilized) or very still, and that the flux through HSC and progenitor (HSPC) populations is likely to be dramatically altered (Vainieri et al, 2016). Furthermore, results presented by Delfim Duarte from her laboratory highlighted the increasing migratory behavior of leukemia cells from early bone marrow infiltration to overt chemoresistance and their relationship with bone marrow niches known to maintain HSCs (Hawkins et al, 2016). In keeping with this theme, Paul Frenette (Albert Einstein College of Medicine, New York, USA) emphasized a complex interplay between niche cells and hematopoietic cells in the bone marrow under steady state conditions in the adult.…”
Section: Hematopoietic Stem Cells In the Adultmentioning
confidence: 95%
“…Instead, T-ALL cells exhibit promiscuous distribution in BM and dynamic interactions with BM microenvironments throughout disease development from the early BM seeding to response and resistance to chemotherapy [40]. And, thus, a stochastic mechanism underlying these processes is proposed (Fig.…”
Section: Lscs Hide In Distinct Preferential Niches In Response To Thementioning
confidence: 99%
“…Full infiltration of T-ALL in recipient BM caused dramatic shrinking, blebbing, and apoptosis of osteoblastic cells, and spared blood vessels and nestin + perivascular cells (Fig. 2c) [40].…”
Section: Dissemination Of Malignant Cells Alters Normal Bm Nichesmentioning
confidence: 99%
See 1 more Smart Citation